Medicolegal characteristics of defense injuries in cases of homicides - Rančić, Nemanja; Djurović, Gordana; Pilipović, Filip; Savić, Slobodan (Vojnosanitetski pregled, 2017)
Background/Aim. During the homicidal act, a victim usually tries to defend himself/herself, and due to these attempts he/she could sustain so-called defense injuries, mostly localized on the arms. The aim of this research was to analyze important medicolegal characteristics of defense injuries, particularly regarding their importance in forensic expertise of homicides. Methods. We analyzed autopsies of all homicidal cases with defense injuries in Belgrade during a three-year period. Results. Defensive injuries were registered in 71 victims of murder. The majority (67.61%) of victims with defense injuries were males. About 25% of victims were aged from 21 to 30 years. The majority (60) of victims were not under influence of alcohol. Homicides were mostly (90.14%) performed by mechanical weapons. The highest frequency of defense injuries was noticed in the victims with multiple homicidal injuries localized on the front side of the body. In a half (50.7%) of the cases they were present on both arms of the victim, mostly on the dorsal side of hands and forearms. Bruises were the most frequent form of defense injuries (36.61% out of 71 cases), while incisions, abrasions, gunshot injuries and stab wounds were less common. Conclusion. Determination of defense injuries and their medicolegal characteristics enables collecting of facts that are important for legal estimation of homicide, as well as for adequate sentence at the end of the court procedure